Religion and human rights: A historical dispute - Tamayo, Juan José (2018)
In this lecture the author describes some tensions produced by religious fundamentalisms and the discourse of human rights and democracy. Six difficulties are explained as samples of current troubles disturbing especially religious women’s situation: equality, participation and sexual and reproductive rights are highlighted. In brief, from modern perspectives also the positive role of religions is deemed as well as its involvement in the universal impact of human rights.